(untitled) (Journal of Plant Disease Sciences, 2019)
Trichoderma possess rapid growth and they are widely distributed and have a variety of biological activities including beneficial effects on plant growth and development. Trichoderma has shown a considerably high genetic biodiversity not only at the species level but also at the under species level. Out of fifteen soil samples collected, Trichoderma was isolated from ten soils. These isolates were sub cultured to get pure cultures. After comparing the morphological details of various isolates , they isolates were identified as T.harzianum and T.viride . There were significant differences in community of Trichoderma species from zone to zone and Trichoderma species were isolated from all the locations of zone 3 and 4 whereas, it was isolated from only one location in zones 1, 2, 8 and 9. Soils under different previous crop types also varied with respect to prevalence of Trichoderma where in colonies were obtained from soils among all type of previous crops. Among seven medium black soil samples only 5 soils recorded Trichoderma out of that T. harzianum was the majority species with 4 isolates.